Analysis and Prediction of Pavement Settlement Caused by Jacking Construction of Ultra-Shallow Rectangular Shield Frame Bridge. (28th October 2020) - Hu, Da; Li, Yongsuo; Liang, Xiaoqiang; Wu, Youping; Zhang, Sheng; Yao, Qi
Abstract : The primary purpose of this paper is to analyze and predict the ground settlement law of large-span rectangular shield frame bridge jacking project, to provide a reference for the optimization design and safe construction of similar projects. In this paper, combined with the jacking project of ultra-shallow buried soft soil layer rectangular shield frame bridge, through the on-site monitoring, the settlement deformation law of the longitudinal and transverse sections of the expressway pavement during the jacking construction process is discussed, and the reasons for the large settlement and rebound are analyzed. The basic laws of the road surface settlement with time are summarized. Based on the Kriging spatiotemporal prediction model, the road surface settlement is predicted. The research shows that the transverse settlement trough of the pavement caused by the rectangular shield frame bridge's jacking construction is stable within 15 m–20 m on both sides toward the axis and symmetrical along the coordinate axis and the alignment roughly conforms to the normal distribution. The influence range of settlement trough becomes greater and greater with shield jacking, and the final settlement curve is W-shaped. After comparing the predicted curve with the measured road settlement curve, we found that the two curves are in good agreement, and the prediction result of the Kriging spatiotemporal prediction model is valid, which can reflect the process of road deformation development during the jacking process of the shield.